2019
DOI: 10.1002/bem.22230
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency Analysis of Single Inductive Coil Measurements Across a Gel Phantom Simulation of Internal Bleeding in the Brain

Abstract: The present study is part of an ongoing effort to develop a simple diagnostic technology for detecting internal bleeding in the brain, which can be used in lieu or in support of medical imaging and thereby reduce the cost of diagnostics in general, and in particular, would make diagnostics accessible to economically disadvantaged populations. The study deals with a single coil inductive device to be used for detecting cerebral hemorrhage. It presents a first‐order experimental study that examines the predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The occurrence of bleeding was avoided as much as possible; only minor bleeding was caused during the insertion of the ICP detection probe, and no intervention treatment was carried out after freezing. Some reported studies have shown that intracranial hemorrhage can also cause changes in the ECPS [36][37][38]. It is related to changes in the composition and volume of intracranial contents, which is more complicated than ICP.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of bleeding was avoided as much as possible; only minor bleeding was caused during the insertion of the ICP detection probe, and no intervention treatment was carried out after freezing. Some reported studies have shown that intracranial hemorrhage can also cause changes in the ECPS [36][37][38]. It is related to changes in the composition and volume of intracranial contents, which is more complicated than ICP.…”
Section: Discussionmentioning
confidence: 99%
“…And good results were obtained in clinical experiments ( Kellner et al, 2018 ). In 2018 and 2019, Oziel and colleagues designed a single coil structure, using broadband measurement data to detect stroke, and achieved good results ( Oziel et al., 2020 ; Oziel, Korenstein & Rubinsky, 2019 ; Oziel, Korenstein & Rubinsky, 2020 ). In addition to EIT and MIT, microwave imaging has been used to detect stroke in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…If the magnetic induction signals can provide hints at these two different stages of cerebral edema, this method may become a new indicator for early intervention. On the other hand, the latest research by Oziel et al also showed that the amplitude/phase change has an increase or decrease or even a non-linear trend with the injected blood volume at different measurement frequencies [ 51 54 ]. At present, some studies have begun to use multi-frequency data combined with specific algorithms.…”
Section: Introductionmentioning
confidence: 99%